Iridocorneal endothelial syndrome: iris naevus (Cogan-Reese) syndrome. A case report - Karandikar, Sumita; Patel, Nilay Nitin; Shanbhag, Nita (International Journal of Research in Medical Sciences, 2017)
The purpose is to present a case of iridocorneal endothelium Syndrome with glaucoma and discuss clinical presentation and management strategies. A 45 year old female presented with redness, pain and diminision of vision in left eye. The patient was completely evaluated for the complaints. Slit lamp biomicroscopy revealed semidilated pupil not reacting to light and variation in iris colour pattern. Intraocular pressure was 14mmHg in the right eye and 46mmHg in the left eye. Gonioscopy of the left eye revealed broad based peripheral anterior synechiae. The optic disc of the left eye had a cup of 0.7. Specular microscopy of the left eye showed pleomorphism and polymegathism with multiple guttatae. This case reports the importance of specular microscopy in the evaluation of ICE syndrome and to plan the appropriate management strategies. We performed a trabeculectomy surgery for this patient with a well-functioning bleb to reduce the intraocular pressures following failure of topical anti-glaucoma medications.